A Study on Dividend Pattern of Indian Corporate Firms - Sharma, Dinesh Kr.; Wadhwa, Ritu (Indian Journal of Research in Capital Markets, 2017)
The study undertaken investigated the dividend pattern and trend of Indian corporate firms for the period from 2002-2014. Dividend payment has always been considered as an important decision by corporates. It has been observed that many firms believe that paying dividend does not affect the value of firms, and many assure that dividend payment does enhance the wealth of shareholders. This study attempted to examine what has been the dividend trend of the Indian firms over a period of 12 years. Analysis of dividend trends for a large sample of stocks traded on the Bombay Stock Exchange (BSE) indicated that the percentage of companies paying dividends increased by 28% over a period of 12 years. The number of companies who were in the non-payer group declined by 51%, which indicated that firms moved towards the paying group. t - test was also conducted between payer and non-payer groups, and it was observed that paying of dividend does make a difference to the profitability and other related factors to firms.